Spectroscopic investigation of improved corrosion resistance of nickel due to multilayer graphene coating developed with suitably tilted substrate during CVD. (5th November 2022) - Arya, Abhishek Kumar; Raman, R.K. Singh; Parmar, Rahul; Amati, Matteo; Gregoratti, Luca; Saxena, Sumit
Abstract: The great variability (from remarkable to little) in graphene's ability as a corrosion barrier coating is attributed to the extent of defects and non-uniformity of graphene. This study established the theoretical basis for tailoring the orientation of the metallic substrate with respect to the direction of flow of the incoming precursor gas into the reactor during the chemical vapour deposition (CVD) of uniform graphene film on the substrate. We validated the theoretical basis by demonstration of development of a multilayer graphene coating with considerably improved uniformity and low defect content on a suitably tilted nickel substrate during CVD that provided an effective and durable corrosion resistance to the metal in an aggressive acidic medium. Thorough scanning X-ray photoemission microscopy (SPEM) using synchrotron radiation and Raman spectroscopy enabled the mechanistic understanding of the improved uniformity and low defect content of graphene coating, and their role in considerably improving the corrosion resistance of nickel. Graphical abstract: Image 1